Personalized Bacteria Loaded with Autoantigens for the Enhancement of Tumor Immunotherapy. Issue 11 (19th January 2023) - Wu, Chenghu; He, Wenjuan; Chen, Yue; Cai, Jie; Zeng, Fanjun; Lu, Zidong; Wang, Jilong
Abstract: Currently, tumor immunotherapy is becoming a new revolution in tumor treatment. Generated from tumor cell lysate (TCL) or irradiated tumor cells, the whole tumor antigen‐based vaccines have the possibility to enhance antitumor immune response without survival from immune surveillance in personalized immunotherapy. Here, polydopamine nanoparticles (PDA NPs) after self‐polymerization are covalently coated with TCL to form PDA@CL. Engineered Salmonella (EnS) wrapped with PDA@CL (EnS@PDA@CL) is targeted the localization of the tumor site by intravenous administration. EnS@PDA@CL delivered autologous antigen‐containing nanoparticles to tumor hypoxia regions through blood circulation. The PDA@CL particles promote the maturation of dendritic cells (DCs), thus eliciting the infiltration of whole tumor antigens specific cytotoxic T lymphocytes, significantly triggering antitumor immunity. The tumor regression in the Panc02 mice confirms the therapeutic potential of EnS@PDA@CL in clinical personalized immunotherapy. Abstract : Personalized bacteria loaded with autoantigens significantly inhibited the tumor cell growth by promoting the maturation of dendritic cells (DCs), eliciting the infiltration of cytotoxic T lymphocytes, and leading a long‐term immune memory effect.